Schools and their local religious contexts: building a framework of negotiations through qualitative meta-synthesis - Fancourt, N; Ipgrave, J (Routledge, 2019)
In this article, we consider the relationships between schools and their local religious contexts and develop a new empirically-informed middle-level theory for analysing these relationships as a complex framework of negotiations. This framework is based on a meta-synthesis of qualitative data from forty-five case-studies of schools in Great Britain and Northern Ireland, which were conducted by researchers at University of Warwick between 2009 and 2015 as part of three major projects. The synthesis design was in three stages. First, two main overarching descriptive nodes were identified, each with two sub-nodes: school – comprising school ethos and religious education; local context – comprising local patterns of belief and pupil religiosity. Second, these four sub-nodes were paired with each other to form six dyads of negotiation: four illustrated ‘direct contextualisation’, and two illustrated ‘indirect contextualisation’. The data were re-analysed through this six-fold framework. Examples of each dyad are set out, illustrating both straightforward and challenging circumstances. The value of this dyadic framework for negotiation is considered, in relation to research, policy and practice, especially in theorising contextualisation. Finally, we underline the value of qualitative meta-synthesis in theory generation.